The Influence of Green Manufacturing, Green Advertising, and Greenwashing on the Sustainability of Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2019-2023 - Pratiwi, Wiwik; Hidayat, Malik; Putri, Azahra Pratiwi; Handari, Henni; Arifin, Zainal (Dinasti Publisher, 2025)
The purpose of this study is to analyze the impact of Green Manufacturing, measured through a dummy variable; Green Advertising, evaluated using the net profit margin ratio; and Greenwashing, assessed based on the PROPER ranking, on Corporate Sustainability, which is determined by the dissemination of sustainability reports following the GRI (Global Reporting Initiative) standard. This research utilizes secondary data, focusing on a population of 125 manufacturing companies, with a sample of 50 companies selected using the purposive sampling method, all of which are listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The panel data regression analysis method is applied using Eviews 13 as the analytical tool. The findings reveal that Green Manufacturing and Greenwashing have a positive but statistically insignificant impact on Corporate Sustainability. Conversely, Green Advertising has a negative but also statistically insignificant effect. Unlike prior studies that included Green Accounting as a variable, this research incorporates Green Manufacturing into the analysis of Corporate Sustainability, with differences also seen in measurement techniques and sample selection. This study uniquely employs the PROPER score to evaluate Greenwashing and Environmental Performance. Collectively, these three factors contribute to Corporate Sustainability, emphasizing that a comprehensive approach addressing various green practices is more effective in enhancing Corporate Sustainability.